Thermodynamic and exergoeconomic analysis of energy recovery system of biogas from a wastewater treatment plant and use in a Stirling engine. (April 2016) - Colmenar-Santos, Antonio; Zarzuelo-Puch, Gloria; Borge-Diez, David; García-Diéguez, Concepción
Abstract: The aim of this research it is to show how the biogas biomethanisation from primary and secondary treatment of activated sludge from a wastewater treatment plant (WWTP), can be an alternative renewable energy option from fossil fuels, which offers competitive advantages and points out new horizons for the use of this fuel. This will allow to achieve some important priorities of energy plans in EU countries: to reduce the organic matter deposited in landfills and CO2 emissions and to find viable solutions to minimize the environmental impact of sewage sludge (SS). This study analyses the biogas combustion and energy recovery processes from a thermodynamic, thermoeconomic and exergetic point of view. The results show that the boiler of the process is the main source of irreversibility and exergy destruction. Moreover, the energy and exergy economic value of exhaust gases from the combustion chamber, are significant and worthwhile to be exploited. For this reason, the present study explores the applicability and suitability of integrating a Stirling engine in such process. The study reveals that it is possible to create a small micro-cogeneration system which leads to sustainable waste management and energy savings in the treatment plant itself. Highlights: Biogas biomethanisation from SS represents an alternative renewable energy source. Thermodynamic, thermoeconomic and exergetic analysis of energy recovery process. The main source of irreversibility and exergy destruction is the boiler. Energy and exergy economic value of exhaust gases is significant. Application of biogas obtained to produce steam to power a Stirling engine.